(untitled) (Academic Journal of Internal Affairs, 2020)
The Hungarian Fire Service is 150 years old. On occasion of this significant anniversary an international conference was held at the Ministry of Interior on the 3rd February 2020. Based on my previously submitted topic proposal, I was invited to the event to present the development of domestically produced fire engines from horse-drawn motorized pumps in the 18th century to the present, introducing R16 fire engine. My publication is a written version of this presentation illustrated with pictures, and a limited review material based on the research and creative work of renowned authors.